Sonochemically Modified Lapindo Mud Using Sulfuric Acid for Efficient Adsorption of Phenol in Aqueous Media and Real Wastewater Samples - Wijaya, Karna; Bhagaskara, Adyatma; Sani, Maria Francia Mirabella; Vebryana, Marini Fairuz; Pratama, Fernando Alvaro; Anggraeni, Widuri; Amin, Amalia Kurnia; Ramadhani, Faturrahman Al; Saviola, Aldino Javier (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Pharmaceutical industrial wastewater frequently contains high amounts of phenolic substances, which pose severe threats to the ecosystem and human health. Therefore, efficient removal of these pollutants is urgently needed. In the present work, sulfated Lapindo mud (SLM) was prepared using the sonochemical method and applied as an adsorbent for phenol removal in aqueous media and actual wastewater samples from Code River, Yogyakarta. Modification of Lapindo mud (LM) using sulfuric acid enables it to remove its impurities, resulting in a material containing 78.4% silica (SiO2) and 15.3% alumina (Al2O3). The SLM adsorbent demonstrated sufficient adsorption performance of 49.8% with an optimal initial phenol concentration of 120 mg/L with a contact time of 100 min at pH of 10. The maximum adsorption capacity (qmax) obtained by the Langmuir isotherm model was 27.2 mg/g. The adsorption process follows pseudo-second-order because it has two active sites, Brønsted acid sites (–SiOH and –SO3H) and Lewis acid sites (Si4+). Phenol in base condition undergoes a deprotonation reaction that is stabilized by the acid-active sites of the SLM adsorbent through intermolecular forces. Considering the large adsorption capacity and quick kinetic, the SLM adsorbent can be a promising cheap and green material to remove phenolic substances in wastewater, especially in the river near the medical facility. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).